Pemahaman Jemaat Lokal terhadap Doktrin Alkitab - Rizal Rizal; Susi Yerni; Yonita Lestari Ndun (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The church, as the body of Christ, carries a vital responsibility in shaping the congregation’s understanding of biblical doctrine as the foundation of a sound life of faith. However, in practice, there remains a gap between the theological instruction provided and the congregation’s actual comprehension in daily life. This study aims to analyze the level of understanding among local congregations regarding biblical doctrine, identify the factors influencing this understanding, and examine the discrepancies between teaching and its application in everyday life. This research employs a qualitative approach using a library research method, focusing on the examination of biblical texts, theological works, and relevant academic literature. The findings indicate that the congregation’s level of understanding of biblical doctrine varies and is influenced by internal factors such as spiritual motivation and faith experience, as well as external factors such as the quality of teaching and ecclesiastical leadership. The gap between teaching and understanding is attributed to the lack of contextual and interactive learning methods. This study underscores the importance of continuous and dialogical theological formation within local churches so that congregants may not only comprehend doctrine cognitively but also embody it practically in faith and action. These findings are expected to enrich the field of practical theology and serve as a reference for developing faith education within the church.